Using Job Resources and Job Demands in Predicting Burnout - (:unkn) unknown (ELSEVIER SCIENCE BV, 2013)
The relationship between the individual and his/her work sometimes become complex and in some cases the relationship become a serious problem. One of the problems in todays highly demanding working life is the phenomenon called burnout (Maslach, Schaufeli, and Leiter, 2001). Our study focuses on the relationship between job demands, job resources and the perceived burnout levels of municipality workers. (c) 2013 The Authors. Published by Elsevier Ltd.
Keywords: Burnout; organizational justice; social support; work overload; job autonomy; personal development opportunities; CONSERVATION; PERFORMANCE; EXHAUSTION; ENGAGEMENT; OUTCOMES; STRESS; MODEL